Transceiver Design for MIMO Systems with Individual Transmit Power Constraints - Raja Muthalagu (Institute of Advanced Engineering and Science, 2018)
This paper investigate the transceiver design for single-user multiple-input multipleoutput system (SU-MIMO). Joint transceiver design with an improper modulation is developed based on the minimum total mean-squared error (TMSE) criterion under two different cases. One is equal power allocation (EPA) and other is the power constraint that jointly meets both EPA and total transmit power constraint (TTPC) (i.e ITPC). Transceiver is designed based on the assumption that both the perfect and imperfect channel state information (CSI) is available at both the transmitter and receiver. The simulation results show the performance improvement of the proposed work over conventional work in terms of bit error rate (BER).